Scenario planning in public libraries: a discussion. Issue 4 (2nd October 2018) - Finch, Matt; Ramirez, Rafael
ABSTRACT: The authors explore the use of scenario planning in public libraries via a Q&A discussion. They discuss the impact of unexpected events and unwelcome trends on libraries' future, explain the distinction between scenario work and forecasting, and outline a practical approach to devising and delivering scenario planning activities at a local library level. This discussion, which took place at Oxford University's Said Business School on 23 August 2018, explores the use of scenario planning in public libraries.